2011
DOI: 10.1007/s00424-011-1007-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin modulates renal water reabsorption in vivo through increased AQP2 availability at the apical plasma membrane of collecting duct cells

Abstract: X-linked nephrogenic diabetes insipidus (XNDI), a severe pathological condition characterized by greatly impaired urine-concentrating ability of the kidney, is caused by inactivating mutations in the V2 vasopressin receptor (V2R) gene. The lack of functional V2Rs prevents vasopressin-induced shuttling of aquaporin-2 (AQP2) water channels to the apical plasma membrane of kidney collecting duct principal cells, thus promoting water reabsorption from urine to the interstitium. At present, no specific pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 67 publications
(114 reference statements)
2
80
1
Order By: Relevance
“…In combination with results from others showing a similar effect of lovastatin on urine concentration in normal mice (102), these data provide compelling evidence that a blockade of AQP2 endocytosis can be harnessed to increase urineconcentrating ability, perhaps ultimately in humans. There are of course several caveats before such therapy can be translated to the human condition.…”
Section: Statins Mobilize Aqp2 Trafficking and Increase Urinary Concesupporting
confidence: 68%
“…In combination with results from others showing a similar effect of lovastatin on urine concentration in normal mice (102), these data provide compelling evidence that a blockade of AQP2 endocytosis can be harnessed to increase urineconcentrating ability, perhaps ultimately in humans. There are of course several caveats before such therapy can be translated to the human condition.…”
Section: Statins Mobilize Aqp2 Trafficking and Increase Urinary Concesupporting
confidence: 68%
“…Fluvastatin reduced the isoprenylation of RhoA and Rab5 GTPases, resulting in decreased membrane tethering these proteins and the accumulation of AQP2 at the PM. 53 Because Rab5a was found upregulated in CF bronchial cell lines, 18 it might be useful to ascertain whether statins administration would benefit CF patients bearing mutations that decrease CFTR stability at the apical surface of airway cells.…”
Section: Rab Proteins As Putative Therapeutic Targetsmentioning
confidence: 99%
“…Among the plethora of candidate molecules that could improve the effect of the current therapy for XNDI, we demonstrated that statins induce an AVP-independent accumulation of AQP2 at the plasma membrane of collecting duct cells in vitro and in vivo in both wild type and XNDI mice, greatly improving kidney concentrating ability [23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular risk factors were estimated and the patient was considered eligible for statin therapy. Fluvastatin was chosen because of our previous report showing an effect of this drug on AQP2 plasma membrane expression in the hope that this statin could also ameliorate NDI symptoms [23,27]. Informed consent was obtained prior to entering the subject into this study.…”
Section: Study Protocolmentioning
confidence: 99%